THE METHODOLOGY FOR FOSTERING THE PROFESSIONAL SKILLS OF FUTURE ENGLISH LANGUAGE EDUCATORS IN THE AGE OF DIGITAL INNOVATION AND INFORMATION ADVANCEMENT (Modern education and development, 2025)
In today’s rapidly evolving educational landscape, the preparation of future English language teachers requires a strong focus on professional skill development, particularly in the context of digital innovation and information technologies. This thesis explores effective methodologies for enhancing teacher competencies through the integration of modern digital tools, innovative pedagogical strategies, and information-based learning approaches. The study highlights the significance of equipping pre-service teachers with essential skills to navigate contemporary teaching challenges and engage students effectively in the digital era.